Why buy the real deal? An investigation into the motivation of young Indian middle class women to purchase authentic luxury bags over counterfeit ones. - Dewan, Rashi (2012)
The luxury market, once a niche one is now undergoing a dynamic growth. People all over the world purchase some or the other luxury product. A lot of research has been done on motivation of people to purchase luxury products and plenty literature is available on why people purchase counterfeit products. It is often viewed that people who cannot afford to buy luxury products in their salary save money to buy it, yet no research is done questioning why these people save money to buy something which is not even an investment and is often just a bag. In this dissertation I have tried to find out if the Indian middle class can afford luxury bags and if they cannot then why do they prefer buying original luxury bags rather than counterfeit ones. The study was done with the help of seventeen in-depth qualitative interviews which measured the weightage of several factors such as quality, ethics, face consciousness, importance of buying experience in order to understand the reasons of participants to purchase authentic luxury bags and not counterfeits. It was found that the main reason for young Indian women to purchase authentic luxury bags is that they do not want to risk loss of face in front of their friends and relatives.